Amazon Rainforest Deforestation and Indigenous People Movement in Preserving Environmental Conservation - Muhtadi Muhtadi; Evy Nurinayah; HS Tisnanta (International Journal Labs, 2022)
Background: The Amazon forest is one of the areas experiencing the largest deforestation in the world and this causes a decrease in environmental quality that occurs in its region, and Brazil is responsible for half of the deforestation in the Amazon because deforestation in the Brazilian Amazon region has the largest percentage compared to other regions. Objective: In line with the formulation of the problem described above, the purpose of writing this paper is to find out why there is a decline in environmental quality and how the role and efforts of Brazilian indigenous people are to protect the environment in the Amazon Forest region. Method: The researchers used qualitative approach here. The data were obtained from various documents, including journals and news from different platforms. The researcher analyzed the data by reading every document thoroughly and concluding the result. Result: The result of the conversion of forest land in the Amazon is that other lands are easier and faster to evict as well when compared to the first time this exploitation activity was carried out in the 1970s to mid-2000s. Large areas of rainforest in the Amazon were eventually filled with livestock, soybean farming, excavation of dams and minerals, as well as clearing of land for urban projection and colonialization projects. Conclusion: From this writing, it can be concluded that the deforestation that occurs in the Amazon Forest is caused by human activities or irresponsible parties who turn the forest into land for personal gain.